Langmuir-schaefer films for aligned carbon nanotubes functionalized with a conjugate polymer and photoelectrochemical response enhancement - Sgobba, Vito; Giancane, Gabriele; Cannoletta, Donato; Operamolla, Alessandra; Omar, Omar Hassan; Farinola, Gianluca M.; Guldi, Dirk Michael; Valli, Ludovico (ACS Applied Materials and Interfaces, 2014)
Single-walled carbon nanotubes (SWCNTs) were suspended in 1,2-dichloroethane by noncovalent functionalization with a low-band-gap conjugated polymer 1 alternating dialkoxyphenylene-bisthiophene units with benzo[c][2,1,3]thiadiazole monomeric units. The suspended 1/SWCNT blend was transferred onto different solid substrates by the Langmuir-Schaefer deposition method, resulting in films with a high percentage of aligned nanotubes. Photoelectrochemical characterization of 1/SWCNT thin films on indium-tin oxide showed the benefits of SWCNT alignment for photoconversion efficiency. © 2013 American Chemical Society.